The Prospect of “Halal Tourism” Destination: An Strategy for Ponorogo Regency, East Java (Indonesia) - Muhammad Ridlo Zarkasyi; Dhika Amalia Kuniawan; Dio Caisar Darma (ASEAN Journal on Hospitality and Tourism, 2021)
Tourism is a prima donna sector that has a major contribution to the economy of the people and Indonesia's state income. Foreign tourist visits to Indonesia rank fourth in ASEAN, contributing to a GDP of 4.25% (Central Bureau of Statistics of Indonesia, 2020). In 2019, the number of Indonesians who are Muslim is 39.8 million and that is the majority, so tourism in East Java is very important to revitalize the concept of “halal tourism”, including for Ponorogo Regency. At this opportunity, the study concentrated on tourism objects in the Ponorogo Regency using the PESTLE method (political, economic, social, technological, legal, and environmental) to identify aspects that can meet the requirements of halal tourism. In general, this is a way of expanding and encouraging East Java Province to become an area capable of implementing halal tourism throughout its Regency by meeting certain criteria set by the Ministry of Tourism of the Republic of Indonesia. The weaknesses and limitations of the study have become a symbol of concern for future improvement. The concept of “halal tourism” is interpreted more broadly in various aspects, not only limited to religious tourism, pilgrimage, or visiting places of worship, but is applied to tourism objects that focus on the sharia process through various aspects. “halal tourism” has great potential to be realized, one of which is in Ponorogo Regency